2000
DOI: 10.1002/1096-9888(200012)35:12<1407::aid-jms72>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated methyl cation (CF3+, CFH2+)-alkyl nitrile cluster ions

Abstract: Ion-molecule reactions of CF(3)(+) or CFH(2)(+) with an acetonitrile-butyronitrile mixture yield product cluster ions in which the two neutral molecules are associated with the cation. The structures of the ion-molecule product ions were investigated by collision-induced dissociation in a multi-quadrupole mass spectrometer. The cluster ions fragment by loss of one neutral alkyl nitrile. The abundance of the fragment ions shows an unexpected inverse correlation with the proton affinity of the alkyl nitrile. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…The dilute gas-phase environment of mass spectrometers, in which a great variety of long-lived gaseous ions can be formed and isolated, has been used to conveniently measure many intrinsic kinetic isotope effects. [29][30][31][32][33][34][35] The isotope-mixed gaseous ions + CH 35 Cl 37 Cl and + CH 79 Br 81 Br give us the opportunity to measure the kinetic effect of [Ar-CHX] + functionalization. In reactions of + CH 35 Cl 37 Cl (Figure 5a), the [Ar-CH 37 Cl] + functionalization of benzene (m/z 127) is found to be slightly more favored than the [Ar-CH 35 Cl] + functionalization (m/z 125).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dilute gas-phase environment of mass spectrometers, in which a great variety of long-lived gaseous ions can be formed and isolated, has been used to conveniently measure many intrinsic kinetic isotope effects. [29][30][31][32][33][34][35] The isotope-mixed gaseous ions + CH 35 Cl 37 Cl and + CH 79 Br 81 Br give us the opportunity to measure the kinetic effect of [Ar-CHX] + functionalization. In reactions of + CH 35 Cl 37 Cl (Figure 5a), the [Ar-CH 37 Cl] + functionalization of benzene (m/z 127) is found to be slightly more favored than the [Ar-CH 35 Cl] + functionalization (m/z 125).…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] The isotope-mixed gaseous ions + CH 35 Cl 37 Cl and + CH 79 Br 81 Br give us the opportunity to measure the kinetic effect of [Ar-CHX] + functionalization. In reactions of + CH 35 Cl 37 Cl (Figure 5a), the [Ar-CH 37 Cl] + functionalization of benzene (m/z 127) is found to be slightly more favored than the [Ar-CH 35 Cl] + functionalization (m/z 125). Hence, the H 35 Cl loss from the intact adduct is slightly faster than the H 37 Cl loss, which characterizes a normal kinetic isotope effect (K i ) 1.025).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…127 The results of several studies on S N 2 reactions within clusters were reported. [128][129][130] Dimeric ions composed of the alkyl nitriles, acetonitrile (CH 3 CN) and butyronitrile (C 3 H 7 CN), and the methyl cation (CH 3 + ) do not have weakly bound structures such as 51 and 52 which interconvert via S N 2 reactions, but rather consist of a methylated nitrile which is covalently bound to the second nitrile as shown in 53 and 54. 128 A similar situation holds for clusters formed from acetonitrile and butyronitrile, and the fluorinated methyl cations (CF 3 + , CFH 2 + ).…”
Section: Scheme 12mentioning
confidence: 99%
“…128 A similar situation holds for clusters formed from acetonitrile and butyronitrile, and the fluorinated methyl cations (CF 3 + , CFH 2 + ). 129 An S N 2 reaction has been observed when binary clusters composed of NF 3 and CH 3 Cl are allowed to interact with a monochromatized electron beam. 130 The nucleophile, F 2 is generated within an energy region around 2 eV by resonant dissociative electron attachment from the NF 3 component of the cluster and then undergoes the S N 2 reaction with the substrate.…”
Section: Scheme 12mentioning
confidence: 99%